Multi-target mechanisms against coronaviruses of constituents from Chinese Dagang Tea revealed by experimental and docking studies. (28th October 2022) - Zhao, Liyun; Qin, Xubing; Lin, Tingting; Xie, Fuda; Yao, Liyuan; Li, Yulin; Xiong, Binhong; Xu, Zhifang; Ye, Yongchang; Chen, Hongfeng; Qiu, Sheng-Xiang
Abstract: Ethnopharmacological relevance: The leaves of Eurya chinensis （Chinese Dagang Tea）have been consumed as herbal tea for centuries in Guangdong, China, and have also been used to prevent influenza and treat colds and fevers in traditional Chinese medicine. However, there are no reports on the chemical profile and efficacy of its leaves for the treatment of fever and viral infections. Materials and methods: The chemical constituents of Eurya chinensis leaves were isolated and identified by phytochemical study and spectroscopic data, E. chinensis extracts and compounds were evaluated for their antiviral activities by cytopathic effect (CPE) reduction and antibody-based EC50 assay. The antiviral effect of the main component was confirmed by immunofluorescence and transmission electron microscopy. Virtual screening and docking enzyme inhibition experiments were performed to analyze the anti-coronavirus mechanisms of the compounds from E. chinensis leaves. Results: In this study, we found for the first time that E. chinensis leaf extract exhibited inhibitory effects against coronaviruses HCoV-OC43 in vitro . Among 23 monomer compounds isolated from E. chinensis leaf extract, the triterpenoids (betulinic acid, α-amyrin) and the flavonoids (naringenin, eriodictyol and quercetin) showed marked antiviral activity. Microscopic optical analyses further demonstrated that betulinic acid can remove virus particles from HCoV-OC43 infected cells. Virtual screening and docking analysis towards the coronavirus in vogue revealed that betulinic acid was able to bind well to PLpro and Nsp14N7-MTase, and that the flavonoids prefer to bind with PLpro, Nsp3MES, NspP14N7-MTase, Nsp16GTA, and Nsp16SAM. The enzyme inhibition experiments demonstrated that betulinic acid (1 ) exhibited significant inhibition of PLpro and N7-MTase activity of SARS-CoV-2. Conclusion: This study proposes E. chinensis and its triterpenoids and flavonoids as promising potential treatments for coronaviruses. Graphical abstract: Image 1